2020
DOI: 10.1155/2020/5632810
|View full text |Cite
|
Sign up to set email alerts
|

Chest Radiography and Xpert MTB/RIF® Testing in Persons with Presumptive Pulmonary TB: Gaps and Challenges from a District in Karnataka, India

Abstract: Background. In India, as per the latest diagnostic algorithm, all persons with presumptive pulmonary TB (PPTB) are required to undergo sputum smear examination and chest radiography (CXR) upfront. Those with sputum smear positive, sputum smear negative, but CXR lesions suggestive of TB or those with strong clinical suspicion of TB are expected to undergo Xpert MTB/RIF® assay test (also known as CB-NAAT (cartridge-based nucleic acid amplification test)). Objective. To assess what proportion of PPTB who are unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Eight studies were from lower-middle-income countries [ 9 , 31 , 36 , 37 , 40 , 41 , 43 , 46 ], five were from upper-middle-income countries [ 6 , 33 , 34 , 39 , 45 ], six were from high-income countries [ 7 , 8 , 32 , 38 , 47 , 48 ] and two were from low-income countries [ 35 , 42 ]. Four studies had representatives from a mix of countries with different income levels [ 5 , 29 , 30 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were from lower-middle-income countries [ 9 , 31 , 36 , 37 , 40 , 41 , 43 , 46 ], five were from upper-middle-income countries [ 6 , 33 , 34 , 39 , 45 ], six were from high-income countries [ 7 , 8 , 32 , 38 , 47 , 48 ] and two were from low-income countries [ 35 , 42 ]. Four studies had representatives from a mix of countries with different income levels [ 5 , 29 , 30 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, providers missed identifying patients who met criteria to undergo NAAT (up to 54%) [51], particularly patients who were not already taking TB treatment and experiencing treatment failure. While algorithms for TB evaluation, including NAAT, have evolved since some of these studies were published [47], our findings suggest that algorithms that target advanced diagnostic testing to patient subgroups run the risk of excluding eligible patients. Communication gaps were also a problem, with many patients not completing the workup because they were not informed they were undergoing sputum testing or chest X-ray due to concern for TB [44,48,56].…”
Section: Findings Specific To Each Care Cascade Gapmentioning
confidence: 91%
“…c Of these 15 studies, 3 reported on non-pursual of diagnostic workup despite referral [40][41][42], 4 reported on non-completion of sputum microscopy evaluation [43][44][45][46], 2 reported on chest X-ray non-completion [47,48], and 6 reported on non-completion of NAAT, line probe assay, or mycobacterial culture [47,[49][50][51][52][53].…”
Section: Characteristics and Quality Of The Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations